WRESTLING WITH TRADITION: A SOCIOLOGICAL STUDY OF AKHARAS IN AMRITSAR, PUNJAB - Josan, Sartaj Singh; Bajwa, Gurshaminder Singh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This ethnographic study explores the cultural significance, everyday practices and challenges faced by traditional wrestling akharas in Amritsar, Punjab. Drawing on unstructured interviews and field observations conducted across five akharas i.e. Bijli Pehalwan da Akhara, Gol Bagh Akhara, P&T Akhara, Akhara Bajrang Bali Ustaad Kuldeep Pehalwan and Panj Peer Akhara. The paper examines how these male-only spaces serve as enduring sites of physical culture, religious devotion and social identity formation. The research highlights the persistence of the guru-chela tradition, the preparation of wrestling grounds using indigenous methods and the integration of spiritual rituals into daily training routines. Despite the growing popularity of modern gyms and professional training centres, these akharas continue to attract young men seeking discipline, fitness and social recognition. Findings reveal a stark contrast between resource-rich and underfunded akharas, with varying degrees of professionalization, infrastructure and government support. Wrestlers often grapple with economic constraints, lack of state assistance, and threats of urban encroachment, yet many remain committed to sustaining this legacy through voluntary labour, donations and community support. The paper also documents how traditional fitness practices coexist with modern techniques and how social media and competitive wrestling tournaments are shaping contemporary akhara culture. Ultimately, the study underscores the role of akharas as vital institutions preserving Punjab’s wrestling heritage and as lived spaces where the body becomes a site of endurance, masculinity and cultural continuity.